THE INFLUENCE OF GUIDED INQUIRY LEARNING MODEL TOWARDS STUDENTS’ LEARNING ACHIEVEMENT - Mauritha, Siska (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ This research is aimed to discover the influence of guided inquiry learning model to improve students’ learning achievement of direct current and Archimedes law materials. This research used experimental method with Pretest-Posttest Control Group Design. The population of this research was the students of XI grade MAN Meulaboh 1 consisting of five classes with 36 students in each. The sampling methods were determined using random sampling technique that resulted in two classes as the research samples. The data analysis of the students’ learning achievement proved that the N-gain improvement of the students in the experimental class was 79.13%. It is better than the result of the control group which was 61.14%. This thing is because the experimental class gets the guided inquiry learning model.